Protectionism In Economic Policy: Peran Pajak Perdagangan Internasional Dalam Perlindungan Industri Dalam Negeri - S, Angel Icha Leony Lastiur; Salsabila, Diva Nayla; Ayyasi, Sofi; Pangestoeti, Wahjoe (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
In the era of globalisation marked by the creation of free trade flows, many domestic industries face great challenges due to competition with cheaper and more massive foreign products. To overcome this, countries implement protectionist policies, one of which is through the implementation of international trade taxes. This study aims to analyse how international trade taxes play a role in protecting domestic industries, especially infant industries in Indonesia. This research uses a qualitative method based on literature study to explore various academic views, fiscal policies, and related economic realities. The study results show that while international trade tax policy can provide room for growth and fairness for local industries, it also risks causing market disruption, increasing consumer prices, and triggering trade retaliation. Therefore, a more adaptive and sustainable approach is needed through alternative policies such as subsidies, increasing industrial competitiveness, and balancing protection and economic openness.